2009
DOI: 10.1086/600106
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Lipid Emulsion Induces Germination ofCandida albicansand Increases Biofilm Formation on Medical Catheter Surfaces

Abstract: LE-inducible candidal virulence determinants, such as germination and enhanced biofilm production, may help to explain the increased risk of candidemia in patients receiving LE via medical catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 42 publications
(54 reference statements)
1
42
2
1
Order By: Relevance
“…The clinical C. albicans wild-type strain SC5314 (a clinical isolate originally obtained from a patient with disseminated candidiasis [37]) was used in all experiments as a control standard. This strain was selected because it can form robust biofilms and is well characterized genetically (38). In addition, 12 C. albicans clinical isolates resistant to fluconazole by overexpression of drug efflux pumps and/or with mutations in the azole target gene ERG11 (34,35) (Table 1) were used, together with C. albicans mutant strains with mutations in selected transcription factors developed by Homann and coworkers (36) (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical C. albicans wild-type strain SC5314 (a clinical isolate originally obtained from a patient with disseminated candidiasis [37]) was used in all experiments as a control standard. This strain was selected because it can form robust biofilms and is well characterized genetically (38). In addition, 12 C. albicans clinical isolates resistant to fluconazole by overexpression of drug efflux pumps and/or with mutations in the azole target gene ERG11 (34,35) (Table 1) were used, together with C. albicans mutant strains with mutations in selected transcription factors developed by Homann and coworkers (36) (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that certain Candida species in the presence of glucose-containing fluids or lipid emulsion might produce ''slime'' (now commonly referred to as biofilm), potentially explaining the increased proportion of CBSIs among patients receiving parenteral nutrition [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus has previously been reported to be a general risk factor for Candida infections [22]. Yet, glucose is thought to serve as the carbohydrate energy source required by Candida for biofilm formation [25], perhaps necessary to produce the polysaccharide matrix [27], in which organized communities of yeast, hyphae, and pseudohyphae are enclosed [28]. In a study by Bhatt et al [29] they reported administration of broad spectrum antibiotics, indwelling catheter and patients on mechanically ventilator were the major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Treated cells were examined using confocal scanning laser microscopy (2). Germination of C. albicans strains in the presence of different concentrations of GV (0.5ϫ to 5ϫ the individual MIC of each isolate) was compared to that of cells exposed to fetal bovine serum (FBS) (HyClone, Logan, UT), a known inducer of germination (7).…”
mentioning
confidence: 99%